2018
DOI: 10.1038/s41598-018-19786-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of processing on structural, mechanical and biological properties of collagen-based substrates for regenerative medicine

Abstract: The aim of this work was to investigate the structural features of type I collagen isoforms and collagen-based films at atomic and molecular scales, in order to evaluate whether and to what extent different protocols of slurry synthesis may change the protein structure and the final properties of the developed scaffolds. Wide Angle X-ray Scattering data on raw materials demonstrated the preferential orientation of collagen molecules in equine tendon-derived collagens, while randomly oriented molecules were fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 44 publications
(34 reference statements)
6
79
0
Order By: Relevance
“…The pattern is centered, calibrated and integrated along the meridional and equatorial directions, and the corresponding 1D WAXS profiles are displayed in the same figure (yellow curves). As shown in Table 1, as well as in our recent WAXS studies performed on type I collagen [44,45], we found a meridional diffraction peak at q1 = 2.22 ± 0.075 Å −1 (marked as 1 in Figure 3a), corresponding to the distance between amino acidic residues along the c-axis of the helix (d = 2.8 ± 0.1 Å, helical axial periodicity). A further diffraction signal was found orthogonally to it: the equatorial peak at q2 = 0.6 ± 0.05 Å −1 (marked as 2 in Figure 3a), corresponding to the lateral packing (d = 10.65 ± 1 Å) of triple helices which varies with the hydration state of the material.…”
Section: Type I Collagensupporting
confidence: 81%
See 1 more Smart Citation
“…The pattern is centered, calibrated and integrated along the meridional and equatorial directions, and the corresponding 1D WAXS profiles are displayed in the same figure (yellow curves). As shown in Table 1, as well as in our recent WAXS studies performed on type I collagen [44,45], we found a meridional diffraction peak at q1 = 2.22 ± 0.075 Å −1 (marked as 1 in Figure 3a), corresponding to the distance between amino acidic residues along the c-axis of the helix (d = 2.8 ± 0.1 Å, helical axial periodicity). A further diffraction signal was found orthogonally to it: the equatorial peak at q2 = 0.6 ± 0.05 Å −1 (marked as 2 in Figure 3a), corresponding to the lateral packing (d = 10.65 ± 1 Å) of triple helices which varies with the hydration state of the material.…”
Section: Type I Collagensupporting
confidence: 81%
“…The type I collagen here analyzed was derived by commercially available raw flakes extracted from equine tendons through a chemical protocol. The protein was provided by Typeone Srl (Lecce, Italy) [44,45].…”
Section: Methodsmentioning
confidence: 99%
“…Beside the Gaussian-noise affected images, the experimental setups often collect data on two-dimensional arrays, where a Poisson counting statistics accordingly needs a noise reduction. In order to investigate the present approach on such noisy data, we applied the model to denoise XRD patterns collected on the collagen molecules in tendon-derived collagens, where under several biochemical conditions, a super-organization of tissue into triple helices (with a preferred orientation displayed by the π-symmetric partial arcs of Figure 3 replacing the fully 2π-symmetric circles) and a high crystalline domain can trigger mechanical stiffness (for details on sample preparation and experimental setup the interested reader is addressed to [30]). In Figure 3 the XRD patterns are shown.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Figure B exhibits the pair distribution function P(R) as a function of radius R, evaluated from the model by means of the PDFGUI software . Two clear peaks in P(R) are seen in: The peak at 0.288 nm corresponds to the meridional distance d 1 between adjacent amino acid residues, projected along the central axis of the helical structure , or alternatively, to one‐third of the unit height twist of 0.86 nm (Figure C). ( The peak at 1.5 nm corresponds to the equatorial distance d 2 between collagen fibrils in the lateral packing (Figure D) . …”
Section: Resultsmentioning
confidence: 99%